Pengembangan Media Tanya Jawab Truth or Dare Pembelajaran IPAS Untuk SD Kelas V - Afiah, Nirfah; Lian, Bukman; Aryaningrum, Kiki (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to develop learning media using Truth or Dare question and answer cards that are valid, practical, and effective for fifth grade elementary school students. This type of research is the R&D method referring to the ADDIE model. The study was conducted at SD Muhammadiyah Prabumulih. The subjects in this study were fifth grade elementary school students. Based on the validation questionnaire that assessed the appearance of the media, presentation of materials, and use of language as a whole, it obtained a score of 87.5% with a very valid category and was worthy of being tested. The results of the One-to-One questionnaire were 93.5% with a very practical category and the results of the Small Group questionnaire obtained a percentage score of 88% with a very practical category. and Effective results of 86.5%. Based on the results, it was concluded that the Development of Truth or Dare question and answer media for learning science for elementary school students in grade V meets the criteria of valid, practical, and effective. and is worthy of use in the science learning process.